Thermochemical processing of rubber waste to liquid fuel - Kawser, M. J.; Farid, N. A. (Maney Publishing, 2000)
Liquid obtained from solid rubber waste via a thermochemical conversion process is expected to play an important role in the future of energy as high value energy carriers and value added chemicals. The energy density of liquid is higher than raw rubber waste because of both chemical and physical characteristics. The Association of South East Asian Nations (ASEAN) countries, especially Malaysia and Indonesia, generate a significant amount of solid waste in the form of natural rubber. Leading on from the elemental composition and thermal characteristics (obtained via thermogravimetric analysis) of solid rubber waste, the production of pyrolysis liquid oil by a fixed bed pyrolysis technique has been attempted. This is both energy recovery and protection of the environment. The liquid oil may be used directly as raw fuel in diesel engines. The liquid oil was characterised by Fourier transform infrared and gas chromatography-mass spectrometry techniques for its detailed chemical composition. The fuel properties of the derived oil were also analysed and compared with petroleum products.